2008
DOI: 10.1016/j.jpain.2007.12.010
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Placebo-Controlled, Crossover Trial of Cannabis Cigarettes in Neuropathic Pain

Abstract: The Food and Drug Administration (FDA), Substance Abuse and Mental Health Services Administration (SAMHSA), and the National Institute for Drug Abuse (NIDA) report that no sound scientific studies support the medicinal use of cannabis. Despite this lack of scientific validation, many patients routinely use "medical marijuana," and in many cases this use is for pain related to nerve injury. We conducted a double-blinded, placebo-controlled, crossover study evaluating the analgesic efficacy of smoking cannabis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
247
0
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(261 citation statements)
references
References 69 publications
5
247
0
9
Order By: Relevance
“…Peak subjective ratings of dronabinol's drug effects occurred 60 min after administration, whereas dronabinol-induced decreases in pain sensitivity and increases in pain tolerance were highest about 4 h after drug administration, suggesting that the magnitude and time course of these subjective drug effects do not necessarily predict analgesia in the CPT. Clinical studies have demonstrated the analgesic effectiveness of cannabinoids including marijuana and dronabinol in neuropathic pain populations (Svendsen et al, 2004;Abrams et al, 2007;Nurmikko et al, 2007;Wilsey et al, 2008;Ellis et al, 2009;Ware et al, 2010). However, the cannabinoids proved to be less effective in attenuating other pain modalities; dronabinol (5 mg) failed to decrease postoperative pain (Buggy et al, 2003) and sensitivity to a thermal stimulus (Roberts et al, 2006), and a higher dronabinol dose (20 mg) failed to reduce acute inflammatory pain, hyperalgesia (Kraft et al, 2008), or increase pain threshold in a pressure test (Naef et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peak subjective ratings of dronabinol's drug effects occurred 60 min after administration, whereas dronabinol-induced decreases in pain sensitivity and increases in pain tolerance were highest about 4 h after drug administration, suggesting that the magnitude and time course of these subjective drug effects do not necessarily predict analgesia in the CPT. Clinical studies have demonstrated the analgesic effectiveness of cannabinoids including marijuana and dronabinol in neuropathic pain populations (Svendsen et al, 2004;Abrams et al, 2007;Nurmikko et al, 2007;Wilsey et al, 2008;Ellis et al, 2009;Ware et al, 2010). However, the cannabinoids proved to be less effective in attenuating other pain modalities; dronabinol (5 mg) failed to decrease postoperative pain (Buggy et al, 2003) and sensitivity to a thermal stimulus (Roberts et al, 2006), and a higher dronabinol dose (20 mg) failed to reduce acute inflammatory pain, hyperalgesia (Kraft et al, 2008), or increase pain threshold in a pressure test (Naef et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Cannabinoids have long been thought to be effective in reducing pain (Russo, 2008) and findings from doubleblind, placebo-controlled studies have substantiated such hypotheses demonstrating that smoked and vaporized marijuana (Abrams et al, 2007;Ellis et al, 2009;Wilsey et al, 2008Wilsey et al, , 2013, oral D 9 -tetrahydrocannabinol (THC; dronabinol), the primary psychoactive component of marijuana (Mechoulam et al, 1970;Svendsen et al, 2004), and Sativex , an oromucuosal preparation of THC and cannabidiol, decrease subjective ratings of pain in neuropathic pain populations. Because of its recent legalization for medical use in a number of US states (Hoffmann and Weber, 2010), marijuana is now being prescribed therapeutically to manage a wide variety of pain conditions (Reinarman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estas sustancias que mantienen y potencian la transmisión dolorosa, son responsables de la cronificación y amplificación del dolor 36. Al respecto, se evalúa la planta a la forma de cigarrillo o vaporizada comparado con un placebo, observándose un prometedor efecto analgésico, principalmente en aquellos preparados con mayor concentración de THC (9,6%). El problema de estos estudios, es que incluyen una pequeña muestra de pacientes y los cigarrillos empleados contenían distintas concentraciones de THC [37][38][39][40] .…”
Section: Cannabis Y Dolorunclassified
“…3 Cannabinoids (e.g., Dronabinol) are considered as a fourth-line treatment option 3 and more recently, smoked or vaporized cannabis has also been clinically investigated. A PubMed review reveals five recent randomized control trials [4][5][6][7][8] (including two published in the Canadian Medical Association Journal), and two systematic reviews, 9,10 that have evaluated the analgesic efficacy of smoked or vaporized cannabis on neuropathic pain compared to a placebo. While treatment regimens (e.g., potency and dosage) and patient populations (e.g., HIV patients, multiple sclerosis patients) varied across studies, each study recorded significant neuropathic pain relief associated with cannabis treatment.…”
mentioning
confidence: 99%